2015
DOI: 10.1002/mus.24314
|View full text |Cite
|
Sign up to set email alerts
|

Influence of resistance exercise intensity and metabolic stress on anabolic signaling and expression of myogenic genes in skeletal muscle

Abstract: This study demonstrates that both intensity and exercise-induced metabolic stress can be manipulated to affect muscle anabolic signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 57 publications
(127 reference statements)
0
22
0
2
Order By: Relevance
“…Interestingly, Popov et al. () reported a similar trend in p‐AMPK after RE where expression values were significantly higher 45 min after relatively higher intensity RE (~75% 1RM) compared to a reduced expression after lower intensity RE (~50%1RM) at the same time point. Thus, these data suggest a more pronounced expression of p‐AMPK after heavy RE at ~1 h after RE while a slightly delayed, but eventual increase seems to occur after light RE (Popov et al.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly, Popov et al. () reported a similar trend in p‐AMPK after RE where expression values were significantly higher 45 min after relatively higher intensity RE (~75% 1RM) compared to a reduced expression after lower intensity RE (~50%1RM) at the same time point. Thus, these data suggest a more pronounced expression of p‐AMPK after heavy RE at ~1 h after RE while a slightly delayed, but eventual increase seems to occur after light RE (Popov et al.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, these data suggest a more pronounced expression of p‐AMPK after heavy RE at ~1 h after RE while a slightly delayed, but eventual increase seems to occur after light RE (Popov et al. ).…”
Section: Discussionmentioning
confidence: 89%
“…The hypertrophic adaptations reported after chronic resistance training at 30 % 1RM with limited strength increases (Mitchell et al 2012;Ogasawara et al 2013) compared to 80 % 1RM training, may be related to the accumulation of metabolic byproducts that occurs during prolonged peripheral fatigue (Popov et al 2006(Popov et al , 2015. In the present study, the 30 % 1RM resistance exercise required 59 % greater volume, 202 % greater time under load, and 18-45 % greater total muscle activation (iEMG) than the 80 % 1RM exercise.…”
mentioning
confidence: 68%
“…Therefore, resistance exercise at 30 % 1RM may prolong the exposure to metabolites, which may act as a stimulus for muscular hypertrophy. For example, Popov and colleagues (Popov et al 2006(Popov et al , 2015 showed that performing continuous contractions (i.e., no relaxation between repetitions) to failure at 50-54 % 1RM increased lactate concentrations to a greater extent than exercise at 74-80 % 1RM (discontinuous contractions) to failure, and enhanced anabolic signaling, decreased myostatin expression, and increased growth factor-1, and growth hormone (GH) concentrations, all of which promote hypertrophy. Burd et al (2012a) demonstrated that prolonged time under load, compared to resistance training at a normal cadence (1 s concentric, 1 s eccentric), also enhanced muscle protein synthesis.…”
mentioning
confidence: 98%
“…Ahtiainen and colleagues (64) reported acute increases in both MGF and IGF1Ea in response to heavyresistance exercise (5 Â 10RM leg press and 4 Â 10RM squats). Conversely, Popov and colleagues (65) found that only a highintensity stimulus (75% 1RM) was sufficient to acutely increase MGF levels, with no changes observed in response to a moderate intensity [50% 1RM] and no changes in IGF1Ea reported in either condition. Although further research is required to determine the contribution of the IGF axis to anabolic adaptation, it is generally thought that improvements are mediated through local rather than systemic expression (36,66) with MGF the primary regulator of these processes in response to exercise (43,67,68).…”
Section: Mechanistic Determinants Of the Exercise Responsementioning
confidence: 94%